Joint action on mental health at the workplace : situation analysis and recommendation for action: - Fine, A.; Griffiths, J.; Breucker, G.; Sochert, R.; Knoche, K.; Zabrocki, H.; Heigi, C.; Radonic, E.; Mattila-Holappa, P.; Buffet, M.A.; Houtman, I.L.D.; Gründemann, R.; et al. (Brussels: The Joint Action, 2015)
The thematic “Mental Health at Workplaces” is part of the “Joint Action on Mental Health and Well-being”, an initiative which sits within the framework of the 2 nd European Health Programme of the European Commission and the Member States of the EU in the period 2013 to 2016. The main aim of this joint action project is to ‘develop an action framework to support enterprises in adopting policies and practices which prevent mental ill-health and strengthen positive mental health’. This objective will be achieved by working with the representatives of eleven participating member states and their relevant stakeholders. The member states involved are Austria, Croatia, Finland, France, Germany, Hungary, Ireland, Iceland, Malta, Netherlands and Slovenia. The planned action will focus not on practices at enterprise level but on how the various stakeholders (apart from enterprises) can put in place a framework and supportive infrastructure which encourages enterprises to adopt initiatives that supports employees with mental health problems and promotes a positive corporate culture that prevents mental health at work.